2014
DOI: 10.1007/s00232-014-9723-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α1-Adrenoceptor Agonist Phenylephrine on Swelling-Activated Chloride Currents in Human Atrial Myocytes

Abstract: Swelling-activated chloride currents (ICl.swell) play an important role in cardiac electrophysiology and arrhythmogenesis. However, the regulation of these currents has not been clarified to date. In this research, we focused on the function of phenylephrine, an α1-adrenoceptor agonist, in the regulation of I(Cl.swell) in human atrial myocytes. We recorded I(Cl.swell) evoked by a hypotonic bath solution with the whole-cell patch-clamp technique. We found that I(Cl.swell) increased over time, and it was difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Nonetheless, PKC stimulated I Cl.vol in canine atrial myocytes (Du and Sorota, 1999) and mouse ventricular myocytes (Gong et al, 2004). Similarly, a recent report demonstrated that I Cl.vol was increased by 100 μM phenylephrine via activation of α 1 -adrenoceptor and PKC in human atrial myocytes (Li and Du, 2015). The present study demonstrated that I Cl.vol up-regulation by noradrenaline was not affected by blocking α 1 -adrenoceptors with prazosin.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Nonetheless, PKC stimulated I Cl.vol in canine atrial myocytes (Du and Sorota, 1999) and mouse ventricular myocytes (Gong et al, 2004). Similarly, a recent report demonstrated that I Cl.vol was increased by 100 μM phenylephrine via activation of α 1 -adrenoceptor and PKC in human atrial myocytes (Li and Du, 2015). The present study demonstrated that I Cl.vol up-regulation by noradrenaline was not affected by blocking α 1 -adrenoceptors with prazosin.…”
Section: Discussionsupporting
confidence: 85%
“…To determine whether noradrenaline-augmented I Cl.vol was due to α 1 -adrenoceptor activation, as observed with a high concentration of phenylephrine (Li and Du, 2015), the α 1 -adrenoceptor antagonist prazosin (2 μM) was applied during cell swelling in 0.6 T solution. Figure 2A shows the time course of I Cl.vol recorded with a ramp protocol (as in Figure 1A).…”
Section: Effects Of αAnd β-Adrenoceptor Antagonists On Stimulation Of I Clvol By Noradrenaline In Human Atrial Myocytesmentioning
confidence: 99%
See 1 more Smart Citation